Battleship [videorecording (DVD)] - Berg, Peter, 1964-; Neeson, Liam; Rihanna, 1988-; Decker, Brooklyn, 1987- (Universal Studios Home Entertainment, 2012)
Based on the classic Hasbro naval combat game, Battleship is the story of an international fleet of ships who come across an alien armada while on a naval war games exercise. An intense battle ensues over sea, land, and air.